HIV/AIDS Training and Skills of Infectious Disease Fellows Among 33 US Academic Institutions. (4th October 2017) - Hicks, Charles; Johnson, Steven C; Daar, Eric; Heggen-Peay, Cherilyn; Sapir, Tamar; Moreo, Kathleen
Abstract: Background: In U.S. internal medicine residency program studies, residents indicated low self-assessed HIV training adequacy, patient care experience, and clinical skills competence. Little is known for infectious disease (ID) fellows, but review findings indicate that increased healthcare provider (HCP) experience and training are associated with better patient outcomes. As part of a continuing medical education (CME) program on HIV, we conducted a survey study in which ID fellows rated their training adequacy, comfort level, and experience in HIV patient care. Methods: On October 1, 2016, an 8 hour workshop was attended by 33 ID fellows from across the US, selected by their program directors. Three HIV experts designed and led the workshop of interactive presentations, case-based discussions, and Q&A. Pre-program surveys included items for trainees to report their experience in providing HIV patient care and to rate their training adequacy and comfort level for clinical skills related to the educational topics. Post-program surveys included items assessing educational outcomes in these domains. In addition to describing the trainees' self-assessments, the associated relationship between trainees' experience in providing patient care and comfort level in performing HIV-related clinical skills were analyzed. Results: Many ID fellows reported little experience (≤15 patients) from their fellowship training in personally counseling patients for PrEP (91% of fellows) and initiating and monitoring patients on guideline-directed ART (51%). Only 30% and 22% of fellows strongly felt that they had adequate experience from their fellowship training in PrEP and guideline-directed ART, respectively. Following the educational program, 55% of fellows strongly agreed that they now felt comfortable in both of these areas. Few ID fellows reported that their training provided adequate experience in discussing sexual risk behavior and preferences (39%), individualizing ART (22%), and avoiding/managing drug-drug interactions (9%). However, following the program, more ID fellows reported feeling comfortable in these areas – 55%, 45%, and 21%, respectively. Conclusion: Gaps persist for ID fellows in training adequacy, comfort level, and experience in HIV patient care. Disclosures: C. Hicks, Merck: Consultant and Scientific Advisor, Consulting fee; Gilead Sciences, Inc.: Consultant and Scientific Advisor, Consulting fee; Janssen: Consultant and Scientific Advisor, Consulting fee; ViiV: Consultant and Scientific Advisor, Consulting fee; E. Daar, Bristol-Myers Squibb: Consultant, Consulting fee; Gilead Sciences, Inc.: Consultant, Grant Investigator and Scientific Advisor, Consulting fee and Research support; Janssen: Consultant, Grant Investigator and Scientific Advisor, Consulting fee and Research support; Merck: Consultant, Grant Investigator and Scientific Advisor, Consulting fee and Research support; Teva Pharmaceuticals: Consultant and Scientific Advisor, Consulting fee; ViiV: Consultant, Grant Investigator and Scientific Advisor, Consulting fee and Research support; C. Heggen-Peay, PRIME Education, LLC: Independent Contractor and Independent medical education provider, Educational grant; T. Sapir, PRIME Education, LLC: Independent Contractor and Independent medical education provider, Educational grant and This project was funded by independent educational grant from Gilead Sciences, Inc. The study sponsors did not play a role in the design or analysis of the study or in the decision to submit for presentation.; K. Moreo, PRIME Education, LLC: Independent Contractor and Independent medical education provider, Educational grant and This project was funded by independent educational grant from Gilead Sciences, Inc. The study sponsors did not play a role in the design or analysis of the study or in the decision to submit for presentation.